Evidence of the Avant Garde since 1957 : Selected Works from the collection of Art Metropole including audio tapes, records, videotapes, film, mutiples, kitsch, manuscripts, stamps, buttons, flyers, posters, correspondence, catalogues, porn, t-shirts, postcards, drawings, poems, mailers, books, photographs and ephemera. - Goodwin, John; Ritchie, Christina (Toronto : Art Metropole, 1984)
Acconci, Vito ; Agnetti, Vincenzo ; Alexander, Shelagh ; Anderson, Laurie ; Andre, Carl ; Art & Language ; Art Propaganda ; Barry, Robert ; Bartolini, Luciano ; Beuys, Joseph ; Borofsky, Jonathan ; Brecht, George ; Brouwn, Stanley ; Buren, Daniel ; Clemente, Francesco ; etc.
Evidence of the Avant Garde since 1957 : Selected Works from the collection of Art Metropole including audio tapes, records, videotapes, film, mutiples, kitsch, manuscripts, stamps, buttons, flyers, posters, correspondence, catalogues, porn, t-shirts, postcards, drawings, poems, mailers, books, photographs and ephemera, An Art Metropole 10th Anniversary event, Art Metropole, Toronto, November 17 to December 8, 1984
English
kunstcatalogus